Transform IT Governance and Management to Enhance Information Security using COBIT Framework 2019 - Achmad Najib Ibrahim; Erma Suryani (Universitas Komputer Indonesia, 2026)
Rapid IT utilization at PT Kawasan Industri Terpadu Batang (KITB) increases cybersecurity risks and compliance demands, requiring structured governance. This study analyzes existing conditions, identifies gaps, and develops an information security governance model using the COBIT 2019 framework. The method involves Design Factor assessments and organizational needs analysis, prioritizing four objectives: EDM03, APO12, APO13, and DSS05. Data gathered via interviews, questionnaires, and document studies evaluated as-is capabilities against to-be targets. Results indicate current capabilities are at Level 3 (Largely Achieved), leaving a one-level gap from the Level 4 target. Consequently, a strategic roadmap focusing on governance, risk management, and security operations was developed to enhance cyber resilience, industrial estate stability, and regulatory compliance.